Modelagem e análise dinâmica de topologias de microrredes CC operando com estratégia de controle hierárquico - Silveira, Rafaela Dizaro (2023)
Microgrids have been considered a promising alternative for structures to contribute to the modernization of the electricity sector, providing a system that integrates and enables the proper functioning of distributed energy resources (REDs), capable of operating the electrical grid in an interconnected and islanded manner. Microgrids powered by direct current (DC) have stood out for the possibilities of offering benefits of improved energy efficiency, cost reduction and simpler control. To enable the connection interface of DERs in a DC microgrid, power electronic converters are commonly used, and coupled to each other through an electrical network, implying the existence of dynamic interactions between the converters and their control loops and other elements such as loads, line impedances, as well as the AC mains. Understanding these interactions is a crucial criterion for understanding the characteristics of the system, properly implementing control strategies, and above all, guaranteeing the stability of the microgrid's DC bus voltage. Therefore, this work presents the development of detailed mathematical models of dc microgrid topologies, considering the dynamics of each subsystem in the microgrid. The studies are conducted for different network configurations, resulting in three different DC microgrid topologies: the single-bus topology, the radial topology, and the ring topology. For ensuring voltage regulation needs on the microgrids, load sharing and energy flow management, a two-level hierarchical control strategy is adopted, where the primary level is based on decentralized control by droop, while the secondary level is based on cooperative distributed control. Thus, each dynamic’s representation and particularities are evidenced using small-signal modeling method and state-space representation. Next, studies of the parameters that can affect the stability of the systems are presented through the identification of the eigenvalues of the studied systems. The performances of the DC microgrids are validated through the development of experimental prototypes, and a comparative analysis involving technical-operational aspects is provided.